Volunteerism in civil society: The world experience and the media - Naumovski, Ljupcho Bozo; Naumovska, Simona Ljupcho, Mo (ASEAN Journal of Community Engagement, 2022)
Volunteering is an important institution for social, cultural, economic, and ecological development, and an effective means for the socialization of the youth and the intellect in the country. The labor proposes a job, that is, defining the essence of the modern phenomenon—volunteering as a value-semantic complex based on the idea of charity, voluntary service in society, and the manifestation of the socially significant free activities of an individual, the group, or organization. This paper discusses the main characteristic features of the evaluative development of volunteering in various historical periods worldwide. Encouraged by these, Macedonian institutions have developed programs for volunteer development with ten-year prospects, considering the regional component and the specificity of the future professional activity of persons who will work in programs abroad. The methodological bases of the research are systematic, institutional, and common approaches and activities.